Legal Certainty for E-Commerce Transactions as an Effort to Increase Potential State Revenue in the Taxation Sector - Hisam Ahyani; Manswab Mahsen Abdulrahman (ISNU Sumatera Utara, 2024)
The development of information technology has driven the growth of e-commerce transactions significantly in Indonesia. However, the rapid growth of e-commerce transactions has also created new challenges in terms of legal certainty and tax collection. Although the government has issued several regulations related to e-commerce, there are still legal loopholes that hinder the optimization of state revenues in the taxation sector. This study aims to analyze the legal certainty of e-commerce transactions as an effort to increase the potential for state tax revenues. The research method used is normative juridical, with a statutory, conceptual, and comparative approach. Research data were collected through literature studies and document analysis involving laws and regulations related to tax and e-commerce, including the Taxation Law, Regulations of the Minister of Finance, and relevant international regulations. The analysis focused on the legal certainty of e-commerce transactions and their implications for state tax revenues. The results of the study indicate that despite regulatory efforts, there is still legal uncertainty caused by the lack of harmonization between tax regulations and e-commerce regulations. This results in difficulties in identifying tax objects, tax subjects, and collection mechanisms. In order to increase the potential for state revenues, steps are needed to strengthen legal certainty, including regulatory updates, increasing cooperation between related institutions, and e-commerce actors and the public. The conclusion of this study emphasizes the importance of legal certainty in e-commerce transactions to support the optimization of state revenues in the taxation sector. Suggestions given include the need for regulatory harmonization, the use of technology to facilitate tax collection, and stricter supervision of digital transactions. Thus, it is hoped that the potential for state revenues from the e-commerce sector can be maximized.